Study of mode of delivery and maternal morbidity in preterm and term COVID-19 positive pregnant women - Dholakiya, Saksha; Singh, Pooja S.; Bamniya, Jaishree; Doshi, Haresh U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pregnant women are likely to represent a high-risk population during current coronavirus 2019 pandemic caused by severe acute respiratory syndrome coronavirus-2. The aim and objective of this study was to evaluate how COVID-19 pandemic has affected the mode of delivery and whether complications of the disease and mortality rate are higher in pregnant women than in non‐pregnant women. Methods: This ambispective observational study was conducted in department of obstetrics and gynaecology of our institute. Pregnant women diagnosed with positive for COVID-19 via the SARS-CoV-2 RT-PCR test in the third trimester and all neonates with complete COVID-19 testing and delivery data. This data was analysed. Results: Out of total 66 cases studied, 48 patients (72.7%) were asymptomatic, while 13 (19.7%) had mild respiratory or gastro intestinal symptoms on initial assessment at admission, including cough, sore throat, fever, weakness or diarrhoea. Cesarean sections were performed in 57.6% of cases. There were no cases of maternal or neonatal mortality. Conclusions: The study revealed that COVID-19 positive pregnant women are usually asymptomatic or mild-moderately symptomatic, similar to COVID-19 positive non-pregnant women. There was a noted rise in the rate of caesarean sections as a mode of delivery.